Biofertilizers technology for rice based cropping system - National Workshop on Recent Developments in Biofertilizers for Rice Based Cropping System (2001 Coimbatore, India); Kannaiyan, S. (Sadasivam) 1944-.; Govindarajan, K.; Kumar K. Dr.; Tamil Nadu Agricultural University (Jodhpur Scientific Publishers, India, 2004)
In the Indian context; contributed papers presented at the National Workshop on Recent Developments in Biofertilizers for Rice Based Cropping System, held during August 16-18, 2001, at Tamil Nadu Agricultural University, Coimbatore, India.
Includes statistical tables.
Includes bibliographical references.